Principles of Entrepreneurship (ENT530): Case Study: Mahatima Batik / Che Ku Maisarah Che Ku Mahhadi … [et al.] - Che Ku Mahhadi, Che Ku Maisarah; Ismail, Hannah Suraya; Zulkernain, Khairunnisa; Adanan, Aida; Zulkefly, Nur Arissa Aqilah (2021)
Mahatima Batik, which specialises in batik fabric or kaftans, was the subject of the case study. Our group chose this company because of the traditional methods of making a batik in Kelantan, which has garnered a lot of attention from all over Malaysia. We conducted an online interview with Muhamood, the owner of Mahatima Batik. Mahatima Batik has been selling batik for the past 23 years. Mahatima Batik is a small business with only two employees. It was founded in early 1998. The name Mahatima Batik is derived from the family name: "MA" is an abbreviation for Mamat, "HA" is an abbreviation for Muhamood, and "TIMA" is an abbreviation for Fatimah. All of the preceding names are employed by the company. The family chose Mahatima Batik as the name of their company because it represents the traditional batik that they produce themselves. Muhamood Mamat is the company's manager, according to the organisational chart. He is not only the manager, but also the owner of the company. Rosmiza Diaman is in charge of the position of assistant manager, which is responsible for ensuring that the company's policies are followed as well as optimising profits through cost control. Finally, Syaza Muhamood is in charge of the Operational Manager. The Operations Manager's primary responsibility is to implement appropriate processes and practises throughout the organisation. Mahatima Batik provides their customers with a variety of batik apparel designs such as baju kelawar, jubah batik, and kain pasang batik cotton viscose. Baju kelawar costs RM40, jubah batik costs RM50, and kain pasang batik cotton viscose costs RM110. To help their business run smoothly, Mahatima Batik implemented a few business strategies such as cross-selling more products, pricing strategies, customer retention, and identifying target markets. Mahatima Batik employs the four Ps of marketing: product, price, place, and promotion. Then, to ensure that their goals are met, Mahatima Batik employs a few operational strategies, including customer-driven strategies, quality assurance, and strategic location. In addition, Mahatima Batik won the Fair Price Shop Awards for the category Textile, Batik & Songket in 2006/2007. We also identified this company's SWOT and conducted some research on the findings and discussion.